Surface oxidation in-situ reconstruction method for improving oxidation resistance of copper material
Through the in-situ reconstruction method of surface oxidation, the copper material is treated with a mixed solution of sodium citrate, ethylene glycol, oleamine and deionized water, which solves the problem of oxidation instability of copper material in the natural environment, and improves its oxidation resistance and corrosion resistance, extends its service life and promotes its refunctionalization.
Patent Information
- Application Number
- CN202411886954.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-28
AI Technical Summary
Metal copper is extremely unstable in the natural environment and is prone to surface oxidation, limiting the service life and application scenarios of its functionalized products, and the existing treatment methods violate the concept of sustainable and environmentally friendly development.
Using a method of surface oxidation in situ reconstruction, the in situ repair of the copper material surface is added by adding sodium citrate, ethylene glycol, oleamine and deionized water to the polytetrafluoroethylene liner, and ultrasonic treatment is carried out to form a homogenous solution, and then gas exchange is performed in a glove box filled with inert gas, and finally heat treatment in a blow drying oven to achieve in situ repair and refunctionalization of the copper material surface.
Without affecting the properties of the copper material itself, the surface of copper oxide metal is repaired in situ through a green and pollution-free method, which significantly improves the oxidation and corrosion resistance of the copper material, extends its service life, and realizes its refunctionalization. It is simple to operate and low cost, and is suitable for large-scale applications.
Smart Images

Figure CN119710687A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material surface functionalization, and in particular relates to a method for surface oxidation in-situ reconstruction for improving the oxidation resistance of copper materials. Background Art
[0002] Copper metal has excellent electrical and thermal conductivity, ductility and fatigue resistance, and has become a widely used basic metal material in power transmission, semiconductors, electronic equipment and other fields. One-dimensional copper nanowires and copper nanoparticles are easy to make into complex and variable patterns for product anti-counterfeiting and safer information storage due to their unique optical properties and low price.
[0003] However, metallic copper is extremely unstable (surface oxidation) in the natural environment, which limits the service life of functionalized products and narrows the scope of application scenarios. In addition, the common method for failed metal materials is scrapping, which violates the concept of sustainable and environmentally friendly development. Therefore, it is of great application and economic value to carry out environmentally friendly, non-toxic and low-cost in-situ repair and refunctionalization of surface oxidized metals. Summary of the invention
[0004] The purpose of the embodiments of the present invention is to provide a method for in-situ reconstruction of surface oxidation for improving the oxidation resistance of copper materials, aiming to solve the problems existing in the above-mentioned background technology.
[0005] The embodiment of the present invention is implemented as follows: a method for surface oxidation in-situ reconstruction for improving the oxidation resistance of copper materials, comprising the following steps:
[0006] (1) adding sodium citrate, ethylene glycol, oleylamine, and deionized water into a polytetrafluoroethylene liner and stirring the mixture to obtain a mixed solution, then adding the copper material into the mixed solution and performing ultrasonic treatment to form a homogeneous solution;
[0007] (2) The inner container containing the homogenized solution is transferred to a glove box filled with inert gas, and sufficient gas exchange is performed in the glove box to remove the air remaining in the inner container. Finally, the inner container is placed in a stainless steel reactor and tightened to a safe state;
[0008] (3) The reactor is taken out of the glove box and placed in a forced air drying oven, heated to 120-180° C. and kept warm, and then naturally cooled to room temperature and then the reactor is taken out, centrifuged, washed and dried to obtain a copper material with high oxidation resistance and surface in-situ reconstruction.
[0009] Preferably, the copper material is one or more of copper foil, copper nanowires and copper nanoparticles.
[0010] Preferably, in step (1), the volume ratio of deionized water:ethylene glycol:oleylamine is 1:12:1, and the mass volume ratio of sodium citrate to deionized water is 0.5-1 g / mL.
[0011] Preferably, in step (2), the heating to 120-180° C. and keeping warm is specifically: heating from room temperature to 120-180° C. within 20-40 minutes and keeping warm for 2-24 hours.
[0012] Preferably, in step (2), the washing operation is specifically: washing with anhydrous ethanol and deionized water alternately.
[0013] Another object of an embodiment of the present invention is to provide a copper material with high oxidation resistance, which is prepared by the above method.
[0014] The embodiment of the present invention provides a method for in-situ reconstruction of surface oxidation for improving the oxidation resistance of copper materials. Under the premise of not affecting the properties of the copper material itself, a green and pollution-free method is used to in-situ repair the surface of the oxidized copper metal, thereby achieving the re-functionalization of the copper material and improving the oxidation resistance and corrosion resistance of metallic copper. The method is simple to operate, low in cost, and can be applied on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The optical photograph, X-ray photoelectron spectrum, scanning electron microscope image and Raman spectrum of the copper foil provided in Example 1 of the present invention;
[0016] Figure 2 Optical photographs, X-ray photoelectron spectroscopy, scanning electron microscope images and Raman spectra of the surface reconstructed copper foil provided in Example 1 of the present invention;
[0017] Figure 3 X-ray diffraction patterns of the copper foil and the surface reconstructed copper foil provided in Example 1 of the present invention;
[0018] Figure 4 Cyclic voltammograms of the copper foil and the surface reconstructed copper foil provided in Example 1 of the present invention;
[0019] Figure 5 Tafel plot of the copper foil and the surface reconstructed copper foil provided in Example 1 of the present invention;
[0020] Figure 6 AC impedance diagrams of the copper foil and the surface reconstructed copper foil provided in Example 1 of the present invention;
[0021] Figure 7 A scanning electron microscope image of copper nanowires provided in Example 2 of the present invention;
[0022] Figure 8Transmission electron microscope and high-resolution transmission electron microscope images of copper nanowires provided in Example 2 of the present invention;
[0023] Fig. 9 Transmission electron microscopy and high-resolution transmission electron microscopy images of surface reconstructed copper nanowires provided in Example 2 of the present invention
[0024] Fig.10 The X-ray photoelectron spectrum of copper nanowires provided in Example 2 of the present invention;
[0025] Fig.11 X-ray photoelectron spectrum of surface reconstructed copper nanowires provided in Example 2 of the present invention;
[0026] Fig.12 X-ray diffraction patterns of copper nanowires and surface reconstructed copper nanowires provided in Example 2 of the present invention;
[0027] Fig.13 The AC impedance diagram of the copper nanowire and the surface reconstructed copper nanowire provided in Example 2 of the present invention;
[0028] Fig.14 The Tafel plot of the copper nanowire and the surface reconstructed copper nanowire provided in Example 2 of the present invention;
[0029] Fig.15 The AC impedance diagram of the copper nanowire and the surface reconstructed copper nanowire provided in Example 2 of the present invention;
[0030] Fig.16 Thermogravimetric curves of copper nanowires and surface reconstructed copper nanowires provided in Example 2 of the present invention;
[0031] Fig.17 A scanning electron microscope image and a corresponding transmission electron microscope image of the copper nanoparticles provided in Example 2 of the present invention;
[0032] Fig.18 This is a scanning electron microscope image of copper nanoparticles reconstructed on the surface of the material provided in Example 2 of the present invention;
[0033] Fig.19 A transmission electron microscope image and a high-resolution transmission electron microscope image of the copper nanowires reconstructed on the surface of the material provided in Example 2 of the present invention;
[0034] Fig. 20 X-ray diffraction patterns of copper nanoparticles and surface reconstructed copper nanoparticles provided in Example 2 of the present invention;
[0035] Fig.21 The X-ray photoelectron spectrum of copper nanoparticles provided in Example 2 of the present invention;
[0036] Fig. 22X-ray photoelectron spectrum of surface reconstructed copper nanoparticles provided in Example 2 of the present invention;
[0037] Fig.23 Cyclic voltammograms of copper nanoparticles and surface reconstructed nanoparticles provided in Example 2 of the present invention;
[0038] Fig.24 Tafel plot of copper nanoparticles and surface reconstructed nanoparticles provided in Example 2 of the present invention;
[0039] Fig.25 The AC impedance diagram of the copper nanoparticles and the surface reconstructed nanoparticles provided in Example 2 of the present invention;
[0040] Fig.26 This is a thermogravimetric curve diagram of the copper nanoparticles and surface reconstructed nanoparticles provided in Example 2 of the present invention. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0042] The copper material in the embodiment of the present invention may be copper foil, copper nanowires and copper nanoparticles;
[0043] The preparation method of copper nanowires is as follows: cuprous chloride (2 mmol), potassium bromide (24 mmol) and oleylamine (6 mmol) are added to a three-necked bottle containing 30 mL of ethylene glycol, and ultrasonically treated for 10 minutes to form a homogeneous copper-amine complex; then, the temperature of the heating stage is raised from room temperature L to 110°C under magnetic stirring, and maintained for more than 30 minutes to purify the solvent, and then the temperature is quickly raised to 198°C (12°C / min), and condensed and refluxed for 1 hour; after the reaction is completed, the product is repeatedly filtered and washed with deionized water and anhydrous ethanol for 3 times, and placed in a vacuum drying oven at 60°C for 2 hours;
[0044] The preparation method of copper nanoparticles is as follows: cuprous chloride (2.7 mmol) and trioctylphosphine oxide (6 mmol) are added to a three-necked flask containing 45 mL of oleylamine, and ultrasonic treatment is performed for 10 minutes to form a homogeneous copper-amine complex; in a Schleck system, the three-necked flask is ventilated with nitrogen to ensure that the reaction is carried out in a nitrogen atmosphere; in a nitrogen environment, the mixed solution is raised from room temperature to 125°C, the stirring speed is 700 rpm, and the exhaust is performed for 1 hour; after the reaction is completed, the product is repeatedly filtered and washed 3 times with anhydrous ethanol and chloroform, and placed in a vacuum drying oven at 60°C for 2 hours.
[0045] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0046] Example 1: A method for in-situ reconstruction of surface oxidized copper foil to improve its anti-oxidation performance, the treatment method comprising the following steps:
[0047] (1) Add 1 mL of deionized water, 12 mL of ethylene glycol, 1 mL of oleylamine, and 0.865 g of sodium citrate into the inner container, stir evenly, and perform ultrasonic treatment to form a homogeneous solution;
[0048] (2) The homogeneous solution obtained in step (1) was mixed with a 4 cm 2 The copper foil mixed seal is placed in the inner tank, and the gas exchange and autoclave filling process are completed in the glove box;
[0049] (3) placing the stainless steel reactor in step (2) in a forced air drying oven, heating to 160° C., maintaining at 160° C. for 2 h, and cooling to room temperature;
[0050] (4) The sample is taken out and washed alternately with anhydrous ethanol and deionized water for 3-4 times to obtain a copper foil with surface in-situ reconstruction and corrosion resistance.
[0051] Example 2: A method for in-situ reconstruction of surface oxidized copper nanowires or copper nanoparticles to improve antioxidant performance, the treatment method comprising the following steps:
[0052] (1) Add 1 mL of deionized water, 12 mL of ethylene glycol, 1 mL of oleylamine, and 0.865 g of sodium citrate into the inner container, stir evenly, and perform ultrasonic treatment to form a homogeneous solution;
[0053] (2) mixing the homogeneous solution obtained in step (1) with 20 mg of copper nanowires or copper nanoparticles, sealing and placing the mixture in an inner container, and completing the gas exchange and autoclave filling process in a glove box;
[0054] (3) placing the stainless steel reactor in step (2) in a forced air drying oven, heating to 160° C., maintaining at 160° C. for 2 h, and cooling to room temperature;
[0055] (4) The sample is taken out and washed alternately with anhydrous ethanol and deionized water for 3-4 times to obtain copper nanowires or copper nanoparticles with surface in situ reconstruction and corrosion resistance.
[0056] Example 3: A method for in-situ reconstruction of surface oxidized copper foil to improve its anti-oxidation performance, the treatment method comprising the following steps:
[0057] (1) Add 0.5 mL of deionized water, 6 mL of ethylene glycol, 0.5 mL of oleylamine, and 0.865 g of sodium citrate into the inner container, stir evenly, and perform ultrasonic treatment to form a homogeneous solution;
[0058] (2) The mixed solution obtained in step (1) was mixed with a copper foil with an area of 4 square centimeters and sealed in an inner container, and the gas exchange and autoclave filling process were completed in a glove box;
[0059] (3) placing the stainless steel reactor in step (2) in a forced air drying oven, heating to 160° C., maintaining at 160° C. for 2 h, and cooling to room temperature;
[0060] (4) The sample is taken out and washed alternately with anhydrous ethanol and deionized water for 3-4 times to obtain a copper foil with surface in-situ reconstruction and corrosion resistance.
[0061] Example 4: A method for in-situ reconstruction of surface oxidized copper nanowires or copper nanoparticles to improve antioxidant performance, the treatment method comprising the following steps:
[0062] (1) Add 1 mL of deionized water, 12 mL of ethylene glycol, 1 mL of oleylamine, and 0.567 g of sodium citrate into the inner container, stir evenly, and perform ultrasonic treatment to form a homogeneous solution;
[0063] (2) mixing the mixed solution obtained in step (1) with 20 mg of copper nanowires or copper nanoparticles, sealing and placing the mixture in an inner container, and completing the gas exchange and autoclave filling process in a glove box;
[0064] (3) placing the stainless steel reactor in step (2) in a forced air drying oven, heating to 160° C., maintaining at 160° C. for 2 h, and cooling to room temperature;
[0065] (4) The sample is taken out and washed alternately with anhydrous ethanol and deionized water for 3-4 times to obtain copper nanowires or copper nanoparticles with surface in situ reconstruction and corrosion resistance.
[0066] Performance Test:
[0067] Electrochemical test: The electrochemical test was performed using a CHI660E electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd.) using a traditional three-electrode system: the copper material prepared in Example 1-4 was used as the working electrode, the Pt wire electrode was used as the counter electrode, and the calomel electrode was used as the reference electrode (all potentials were relative to the calomel electrode, the same below). The electrochemical tests were all carried out in a 0.1 mol / L NaOH solution at 25°C, with the potential set to -1.2-0.2 V. The specific test results are shown in Figure 4-6 , 13-15 and 23-25;
[0068] Figure 1In the figure, a and c are optical photos and scanning electron microscope images of copper foil respectively. From a, it can be seen that the original copper foil is dull in color, indicating that a serious oxidation reaction has occurred on its surface. From c, it can be seen that the microscopic shape error of the surface is large, indicating that oxidation has caused serious damage to the metal surface; b and d are the sample copper foil and X-ray photoelectron spectrum and Raman spectrum, which clearly show that the copper foil has more surface oxidation species, and cuprous oxide and cupric oxide peaks appear;
[0069] Figure 2 Figures a and c are optical photos and scanning electron microscope images of the surface reconstructed copper foil, respectively. From a, it can be seen that the surface reconstructed copper foil presents a bright metallic luster, indicating that the surface oxide species are in situ reduced. From c, it can be seen that the surface is very flat, indicating that the in situ repair treatment is very effective in restoring the surface structure of the metal; b and d are X-ray photoelectron spectra and Raman spectra of the surface reconstructed copper foil, which clearly show that no oxide species are detected on the surface reconstructed copper foil;
[0070] Figure 3 The X-ray diffraction spectra of copper foil and surface reconstructed copper foil are shown in Figure 1. The corresponding characteristic peaks are consistent with the standard card. After surface treatment, the peak intensity of the (111) crystal plane of copper foil and surface reconstructed copper foil is enhanced.
[0071] Figure 4 The cyclic voltammetry test of copper foil and surface reconstructed copper foil shows obvious redox peaks in copper foil, while no significant oxidation peaks in surface reconstructed copper foil.
[0072] Figure 5 The Tafal curves corresponding to the copper foil and the surface reconstructed copper foil are shown in Figure 1. The corrosion rate of the copper foil is calculated to be 1.00×10 -3 mm yr -1 The corrosion rate of the copper foil with surface reconstruction is 1.99×10 -3 mm yr -1 ;
[0073] Figure 6 The electrochemical impedance diagrams of copper foil and surface reconstructed copper foil are shown. It can be seen that the AC impedance of surface reconstructed copper foil is significantly better than that of copper foil.
[0074] Figure 7 In the figure, a, b, and c are scanning electron microscope images of copper nanowires, showing high-purity copper nanowires with uniform morphology, and d is an energy spectrum of the sample copper nanowires, showing the distribution of copper elements in the copper nanowires;
[0075] Figure 8 In the figure, a is a transmission electron micrograph of a copper nanowire, and b is a high-resolution transmission electron micrograph of a copper nanowire, where the lattice fringes of the copper nanowire can be clearly seen, and the interplanar spacing is 0.232 nm, which is consistent with the (111) crystal plane of copper oxide;
[0076] Fig. 9 In the figure, a is a transmission electron microscopy image of the surface reconstructed copper nanowires, and b is a high-resolution transmission electron microscopy image of the surface reconstructed copper nanowires. The lattice stripes of the surface reconstructed copper nanowires can be clearly seen, and the interplanar spacing is 0.208nm, which is consistent with the (111) crystal plane of copper;
[0077] Fig.10 This is the X-ray photoelectron spectrum of copper nanowires. It can be seen that there are many oxide species on the surface of the original copper nanowires;
[0078] Fig.11 This is the X-ray photoelectron spectrum of the surface reconstructed copper nanowires. It can be seen that the oxide species of the surface reconstructed copper nanowires are significantly reduced;
[0079] Fig.12 The X-ray diffraction diagrams of copper nanowires and surface reconstructed copper nanowires are shown in Figure 1. The corresponding characteristic peaks are consistent with the standard card. After surface treatment, the peak intensity of the (111) crystal plane of the surface reconstructed copper nanowire is enhanced.
[0080] Fig.13 The cyclic voltammograms of copper nanowires and surface reconstructed copper nanowires show obvious redox peaks in copper nanowires, while surface reconstructed copper nanowires do not show significant oxidation peaks.
[0081] Fig.14 The Tafel diagram of copper nanowires and surface reconstruction of copper nanowires, the corrosion current is reduced from 3.68×10 -6 A (original copper nanowire) dropped sharply to 4.68×10 -7 A (surface reconstructed copper nanowires);
[0082] Fig.15 The AC impedance diagram of copper nanowires and surface reconstructed copper nanowires. It can be seen that the impedance of surface reconstructed copper nanowires is significantly better than that of copper nanowires.
[0083] Fig.16 The thermogravimetric curves of copper nanowires and surface reconstructed copper nanowires. The copper nanowires began to oxidize at 115°C, and the surface reconstructed copper nanowires began to oxidize at 125°C, with a difference of 10°C.
[0084] Fig.17 Figure 1 is a scanning electron microscope image of copper nanoparticles and the corresponding transmission electron microscope image. a and b are scanning electron microscope images, showing high-purity copper nanoparticles with uniform morphology. c and d are transmission electron microscope images and high-resolution transmission electron microscope images of sample copper nanoparticles, showing clearly the lattice fringes of the copper nanoparticles, with a crystal plane spacing of 0.181 nm, which is consistent with the (200) crystal plane of copper.
[0085] Fig.18This is a scanning electron microscope image of surface reconstructed copper nanoparticles. The morphology remains uniform after treatment.
[0086] Fig.19 Transmission electron microscopy and high-resolution transmission electron microscopy images of surface reconstructed copper nanoparticles. It can be seen that the lattice spacing is 0.181 nanometers, which is consistent with the (200) crystal plane of copper;
[0087] Fig. 20 X-ray diffraction patterns of copper nanoparticles and surface reconstructed copper nanoparticles. The (111) diffraction peak is significantly enhanced after surface reconstruction.
[0088] Fig.21 This is the X-ray photoelectron spectrum of copper nanoparticles, which shows a relatively obvious distribution of oxidation species;
[0089] Fig. 22 For the surface reconstruction of copper nanoparticles, the X-ray photoelectron spectrum shows that the content of oxidized species is significantly reduced;
[0090] Fig.23 The cyclic voltammograms of copper nanoparticles and surface reconstructed copper nanoparticles show that the redox peak area is significantly reduced after surface reconstruction.
[0091] Fig.24 Tafel plot of copper nanoparticles and surface reconstruction of copper nanoparticles, corrosion current from 2.16×10 -7 A (original copper nanoparticles) dropped sharply to 4.51×10 -9 A (surface reconstructed copper nanoparticles);
[0092] Fig.25 The AC impedance diagrams of copper nanoparticles and surface reconstructed copper nanoparticles show that the impedance of surface reconstructed copper nanoparticles is significantly better than that of copper nanoparticles.
[0093] Fig.26 The thermogravimetric curves of copper nanoparticles and surface reconstructed copper nanoparticles are as follows. The copper nanoparticles begin to oxidize at 117°C, and the surface reconstructed copper nanoparticles begin to oxidize at 132°C, with a difference of 15°C.
[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for in-situ reconstruction of surface oxidation for improving the oxidation resistance of copper materials, characterized in that: The following steps are involved: (1) adding sodium citrate, ethylene glycol, oleylamine, and deionized water into a polytetrafluoroethylene liner and stirring the mixture to obtain a mixed solution, then adding the copper material into the mixed solution and performing ultrasonic treatment to form a homogeneous solution; (2) The inner container containing the homogenized solution is transferred to a glove box filled with inert gas, and sufficient gas exchange is performed in the glove box to remove the air remaining in the inner container. Finally, the inner container is placed in a stainless steel reactor and tightened to a safe state; (3) The reactor is taken out of the glove box and placed in a forced air drying oven, heated to 120-180° C. and kept warm, and then naturally cooled to room temperature and then the reactor is taken out, centrifuged, washed and dried to obtain a copper material with high oxidation resistance and surface in-situ reconstruction.
2. The method for in-situ reconstruction of surface oxidation for improving the oxidation resistance of copper materials according to claim 1, characterized in that: The copper material is one or more of copper foil, copper nanowires and copper nanoparticles.
3. The method for surface oxidation in-situ reconstruction for improving the oxidation resistance of copper materials according to claim 1, characterized in that: In step (1), the volume ratio of deionized water: ethylene glycol: oleylamine is 1:12:1, and the mass volume ratio of sodium citrate to deionized water is 0.5-1 g / mL.
4. The method for in-situ reconstruction of surface oxidation for improving the oxidation resistance of copper materials according to claim 1, characterized in that: In step (2), the heating to 120-180° C. and keeping warm are specifically: heating from room temperature to 120-180° C. within 20-40 minutes and keeping warm for 2-24 hours.
5. The method for surface oxidation in-situ reconstruction for improving the oxidation resistance of copper materials according to claim 1, characterized in that: In step (2), the washing operation is specifically: washing with anhydrous ethanol and deionized water alternately.
6. A copper material with high oxidation resistance, characterized in that: It is prepared by the method described in any one of claims 1 to 5.
Citation Information
Patent Citations
Method for preparing graphene structure-like copper-indium-sulfur nanosheet array membrane
CN103819099A
Method for purifying copper nanoparticles
CN104057100A
Surface processing method for copper-containing material
CN107460464A
Copper surface treatment liquid and copper surface treatment method for multilayer printed circuit board manufacturing
CN110029336A
Method for enhancing oxidation resistance of body material copper
CN113265662A